Sharing Economy: A Study on the Factors Influencing Users' Motivation to Use Ride Sharing Platforms - Rosdiana Sijabat (DeReMa (Development Research of Management): Jurnal Manajemen, 2019)
This research is intended to explore sharing economy, particularly ride sharing. The study aims to identify the impact of four factors—economic, social, environmental, and technological—on individuals' motivation and decision to use three ride sharing platforms: UBER, GRAB and Go-JEK in Indonesia. Based on available literature, four research hypotheses are tested, namely that (1) economic factors; (2) social factors;(3)  environmental factors; and (4) technological factors have positive influence on individuals' motivation and decision to use ride sharing services. Primary and secondary data are used to answer the research questions. Primary data were obtained through an online survey of 355 respondents, while secondary data were obtained from various related literatures. The research is both descriptive and quantitative in nature, the empirical analysis suggest that economic, social, environmental, and technological factors are positively associated with users' decision to use ride sharing.Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk mengeksplorasi konsep sharing economy, khususnya ride sharing. Secara khusus, studi ini bertujuan untuk mengidentifikasi pengaruh dari empat factor, yaitu faktor ekonomi, sosial, lingkungan, dan teknologi terhadap motivasi dan keputusan individu untuk menggunakan tiga platform perjalanan bersama: UBER, GRAB, dan Go-JEK di Indonesia. Berdasarkan literatur yang tersedia, empat hipotesis penelitian diuji, yaitu bahwa (1) faktor ekonomi; (2) faktor sosial; (3) faktor lingkungan; dan (4) faktor teknologi memiliki pengaruh positif terhadap motivasi dan keputusan individu untuk menggunakan layanan ride sharing. Data primer dan sekunder digunakan untuk menjawab pertanyaan penelitian. Data primer diperoleh melalui survei online terhadap 355 responden, sedangkan data sekunder diperoleh dari berbagai literatur terkait. Penelitian ini bersifat deskriptif dan kuantitatif, analisis empiris menunjukkan bahwa faktor ekonomi, sosial, lingkungan, dan teknologi secara positif terkait dengan keputusan pengguna untuk menggunakan berbagi perjalanan.